Mobilising finance for climate change mitigation : private sector involvement in international carbon finance mechanisms - Lin, Jolene; Streck, Charlotte (Melbourne journal of international law, 2009)
Examination of the role that the private sector plays in the implementation of the United Nations Framework Convention on Climate Change and the Kyoto Protocol - the role non-state actors play in international law - reducing emissions from deforestation and forest degradation (REDD) - private sector involvement in Kyoto Protocol mechanisms.